Comparison of Performance of CAPM vs Fama and French Three-Factor Model vs Fama and French Five-Factor Model for Shanghai Stock Index - Afgun, Mohammad Hassam (2020)
The purpose of this research is to find which Asset Pricing Model amongst CAPM, Fama and French three-factor model, and Fama and French five-factor model best captures the return for the Chinese economy, using SSE180 stock index as the sample. For this purpose, the Right Hand-side (RHS) approach is used. The approach relies on the use of Factor Spanning Regression, which tests for significance of the factors within the model, and GRS test, which checks for mean-variance efficiency. The paper finds that while the performance of the Fama and French factor models is superior to CAPM, no difference can be observed between FF3M and FF5M. This is because the additional two factors the transform the FF3M into FF5M - profitability and investment, are insignificant for the Chinese Market. Foye (2018) explains that most APMs are structured on US economy, and therefore their translation to other markets are not always perfect. Factors which capture the effect on returns for US, might not be the same for others. As is observed in the case of China. The results of this paper finds that financial analyst have to be cautious in adoption of APMs for market analysis, and that there is a strong need for research in construction of domestic variants of APMs that incorporate only factors that are best suited to capture the returns of the country in hand.